Altered cerebrovascular response to acute exercise in patients with Huntington's disease. Issue 1 (16th April 2020) - Steventon, Jessica J; Furby, Hannah; Ralph, James; O'Callaghan, Peter; Rosser, Anne E; Wise, Richard G; Busse, Monica; Murphy, Kevin
Abstract: The objective of this study was to determine whether a single session of exercise was sufficient to induce cerebral adaptations in individuals with Huntington's disease and to explore the time dynamics of any acute cerebrovascular response. In this case–control study, we employed arterial-spin labelling MRI in 19 Huntington's disease gene-positive participants (32–65 years, 13 males) and 19 controls (29–63 years, 10 males) matched for age, gender, body mass index and self-reported activity levels, to measure global and regional perfusion in response to 20 min of moderate-intensity cycling. Cerebral perfusion was measured at baseline and 15, 40 and 60 min after exercise cessation. Relative to baseline, we found that cerebral perfusion increased in patients with Huntington's disease yet was unchanged in control participants in the precentral gyrus ( P = 0.016), middle frontal gyrus ( P = 0.046) and hippocampus ( P = 0.048) 40 min after exercise cessation (+15 to +32.5% change in Huntington's disease participants, −7.7 to 0.8% change in controls). The length of the disease‐causing trinucleotide repeat expansion in the huntingtin gene predicted the change in the precentral gyrus ( P = 0.03) and the intensity of the exercise intervention predicted hippocampal perfusion change in Huntington's disease participants ( P < 0.001). In both groups, exercise increased hippocampal blood flow 60 min after exercise cessation ( P = 0.039). These findings demonstrate the utility of acute exercise as a clinically sensitive experimental paradigm to modulate the cerebrovasculature. Twenty minutes of aerobic exercise induced transient cerebrovascular adaptations in the hippocampus and cortex selectively in Huntington's disease participants and likely represents latent neuropathology not evident at rest. Abstract : Nineteen participants with Huntington's disease and 19 controls underwent MRI before and immediately after a 20-min exercise intervention. A region of interest analysis found that cerebral blood flow was selectively increased in participants with Huntington's disease in the precentral gyrus, middle frontal gyrus and hippocampus 40 min after exercise cessation, suggesting that exercise exposes latent Huntington's disease pathology. Graphical Abstract: